2021
DOI: 10.3126/janr.v4i2.33674
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seed treatment using Mancozeb and Ridomil fungicides on Rhizobium strain performance, nodulation and yield of soybean (Glycine max L.)

Abstract: The viability of commercial Rhizobium strains (SB-14 and SB-12) were inoculated and fungicides (Mancozeb and Ridomil) were used as seed dressed on soybean seed to investigate their effect on nodulation, plant growth and seed yield of soybean. Application of Rhizobial inoculants alone gave the highest nodulation and shoot dry weight performance as well as seed yield of soybean on both sites. SB-12 inoculant had significantly shown to be more effective than SB-14 inoculant in increasing nodulation and thus produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, it should be noted that the ecological parameters assessing diversity and dominance among bacteria did not show significant differences based on the type of cultivation.The cultivation method has a significant effect on bacteria, especially their quantitative representation of the fruit, and indirectly influences their diversity. Previous studies have indicated the negative effect of fungicides on bacteria (reduction in abundance or elimination) (Gu et al, 2010;Getachew and Abeble, 2021;Ma et al, 2021). Consequently, fungicides may reduce bacterial diversity and the number of bacteria on the fruit, potentially weakening the fruit's natural biological defense against pathogens.…”
Section: Influence Of the Viticultural System On The Microbiomementioning
confidence: 99%
“…However, it should be noted that the ecological parameters assessing diversity and dominance among bacteria did not show significant differences based on the type of cultivation.The cultivation method has a significant effect on bacteria, especially their quantitative representation of the fruit, and indirectly influences their diversity. Previous studies have indicated the negative effect of fungicides on bacteria (reduction in abundance or elimination) (Gu et al, 2010;Getachew and Abeble, 2021;Ma et al, 2021). Consequently, fungicides may reduce bacterial diversity and the number of bacteria on the fruit, potentially weakening the fruit's natural biological defense against pathogens.…”
Section: Influence Of the Viticultural System On The Microbiomementioning
confidence: 99%
“…The plants of the family Fabaceae in the symbiosis with nodule bacteria (Rhizobiaceae) form an active symbiotic apparatus, and a combination of all the measures, aimed at the optimization of this process, promotes the realization of their nitrogen-fi xation potential (Joshi et al, 2014). At present, there are active studies on the possibility of using seed inoculation with nodule bacteria prior the planting to regulate the metabolism of legumes and enhance their tolerance to biotic effects (Dicheng et al, 2018;Standish et al, 2018;Alonso-Monge et al, 2020;Laktionov et al, 2020;Rathjen et al, 2020;Getachew et al, 2021;Martinez et al, 2021;Santos et el, 2021).…”
Section: Introductionmentioning
confidence: 99%